Non‐melanoma skin cancer as a clinical marker for internal malignancies: a nationwide population‐based cohort study. (26th November 2019) - Yun, S.J.; Bae, J.M.; Kim, H.; Park, B.C.; Kim, J.S.; Seo, S.H.; Ahn, H.H.; Lee, D.Y.; Kim, Y.C.; Park, H.J.; Chung, K.Y.
Abstract: Introduction: Non‐melanoma skin cancers (NMSCs) are the most common cancers in the world, but the risk of internal malignancy in patients with NMSC has not been well investigated. Objectives: We aimed to assess the risk of internal malignancy in patients with NMSC compared with controls without NMSC in Korean population. Methods: This nationwide cohort study, compared 27 259 NMSC patients with 54 518 matched controls without NMSC, 40 years or older using the data from Korea Health Insurance Review and Assessment Service from 2007 to 2016. The first 2 years were washout period, and we followed the patients for 8 years to observe the development of any internal malignancies after a diagnosis of NMSC. The Cox proportional hazard model was used to determine the hazard ratios (HRs) for developing internal malignancies. Results: The overall risk of internal malignancies at all sites was 2727.7 and 1392.4 per 100 000 person‐years for the patients with NMSC and controls, respectively. The risk was significantly higher in the patients with NMSC (HR 1.866, 95% confidence interval [CI] 1.768–1.970). Bone cancer showed the highest risk (HR 12.745, 95% CI 6.288–25.834), followed by nasal cavity and larynx (HR 10.279, 95% CI 6.178–7.103), oral cavity and pharynx (HR 10.211, 95% CI 7.375–14.137), anus and anal canal (HR 8.147, 95% CI 3.893–17.051) and cervical (HR 5.900, 95% CI 3.694–9.423) cancers with risks greater than fivefold higher in NMSC patients compared with the controls. The risks of cancers of the thorax, oesophagus, breast, lung, stomach, thyroid gland and non‐Hodgkin's lymphoma were also statistically higher in the patients with NMSC. In contrast, the risks of cancers of the colon and rectum were found to be significantly decreased in the patients with NMSC (HR 0.765, 95% CI 0.657–0.890). Conclusion: Patients with NMSC require careful screening and follow‐up for internal malignancy.